Timely completion of childhood vaccination and its predictors in Burkina Faso - Koulidiati, Jean-Louis; Kaboré, Rémi; Nebié, Eric I.; Sidibé, Annick; Lohmann, Julia; Brenner, Stephan; Badolo, Hermann; Hamadou, Saidou; Ouédraogo, Nobila; De Allegri, Manuela (Vaccine, 2022)
Background - Despite important progress in global vaccination coverage, many countries are still facing preventable disease outbreaks. Timely vaccination is important in getting adequate protection against disease. In light of the paucity of relevant literature, this study investigated the timely completion of childhood routine immunization and identified factors associated with timely vaccination in Burkina Faso. - Methods - We extracted data on child vaccination and other child characteristics from a household survey conducted across 24 districts in 2017. We extracted data on health system characteristics from a parallel facility survey. We applied a Kaplan-Meier time-to-event analysis to estimate timely vaccination coverage defined as the proportion of children that received a given vaccine in the period between three days before and 28 days after the recommended age. We used a Cox proportional hazard model with mixed effects to identify factors associated with timely vaccination. - Results - In total, 3,138 children aged between 16 and 36 months who could present an immunization booklet were included in the study.The main finding is the existence of an important gap showing that timely vaccination coverage was lower than vaccination coverage. More specifically,this gap ranged from 16% for BCG to 43% for Penta 3. In addition, region and distance between the household and the nearest health facility were the main factors associated with timely full vaccination coverage and specifically for Penta3, MCV1 and MCV2. - Conclusions - This study highlights that timely vaccination coverage remains substantially lower than vaccination coverage. Timeliness of vaccination should therefore be considered as a metric to assess the status of immunization in a country. Geographical accessibility continues to represent a major barrier to timely vaccination, calling for specific interventions on both supply-side (e.g. outreach activities) and demand-side (e.g. vouchers or community-based interventions for vaccination) to counteract its negative effect.
Gesehen am 03.08.2022